The Role of the Endonasal Endoscope in the Operative Management of Brain Abscess: A Case Report - Sacks, Daniel; Kim, Esther; Russell, Paul (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background The endonasal endoscope has become widely integrated into the operative practice of skull-base surgeons. Although it is not the current standard of practice for the drainage of intracranial abscesses, transnasal neuroendoscopy has the potential for benefit over both stereotaxy and open craniotomy because it is minimally invasive and provides a visual confirmation of debridement. We present two recent cases in which patients with intradural abscesses adjacent to the anterior skull base were successfully drained and irrigated using an endoscopic approach.Case Two patients with post-traumatic intradural brain abscess underwent transnasal neuroendoscopic drainage in a 1-year period. In both cases, the abscesses were drained and irrigated without complication under direct visualization. The patients' outcomes were felt to be positive given their initial insults.Conclusion Transnasal endoscopic drainage of brain abscesses appears to be safe and has particular advantages in specific cases over the current operative standard, which are likely to prove beneficial for patients and cement it as a feasible alternative to stereotactic aspiration and craniotomy.
Keywords: transnasal approach; minimally invasive; endoscopy; skull base